ESTIMATION AND CORRELATION OF LOW FLOW HYDROLOGICAL PARAMETERS USING A NOVEL MODIFIED STORAGE-YIELD-RELIABILITY MODEL FOR MALAYSIAN STREAMFLOW STATIONS - Pan, W.F.; Heng, H.H.; Chan, J.A.; Ong, J. (Journal of Engineering & Technological Advances, 2025)
This study presents a modified methodology to estimate various low flow hydrological parameters of various streamflow stations in Malaysia. This is followed by a subsequent estimation of low flow quantum using a modified storage-yield-reliability (SYR) model. These low flow estimates are crucial in managing the water resources in a river basin. Furthermore, it is also stipulated in the provision of environmental flow (EF) prescription for prior releases in water resources management in Malaysia. The database (90 streamflow stations in Malaysia) adopted in this paper is abstracted from the National Water Resource Study review. This paper presents a novel methodology for low flow yield estimation using Vogel and Kuria’s modified version of the SYR model. The modified version adopts the same formulation and structure as the original multiple regression equation, but with an additional calibration step for deriving the calibrated parameters. The correlation between average annual flow and low flow quotient shows a moderately higher coefficient of determination (r2), varying from 0.724 to 0.850 for various hydrological regions in Malaysia. In addition, fair and consistent correlation is demonstrated, falling within a factor of two line visually using the respective coefficient of determination of the regression equations for various hydrological regions in Malaysia. However, minor noises and fluctuations are observed between the estimated results and the observed dataset and records. This novel modified SYR model’s significant practicality and utility are vividly shown, and it can be readily used in the pre-feasibility water resources study.